The Classification of Inkjet Inks Using AccuTOF™ DART™ (Direct Analysis in Real Time) Mass Spectrometry—A Preliminary Study1. Issue 3 (12th March 2013) - Houlgrave, Stephanie; LaPorte, Gerald M.; Stephens, Joseph C.; Wilson, Justin L.
Abstract A novel approach for the analysis of inkjet inks is being reported. A time‐of‐flight mass spectrometer, coupled with a Direct Analysis in Real Time (DART™) ion source (AccuTOF™ DART™), was used to determine if inkjet inks from various manufacturers and models of printers could be reliably differentiated, characterized, and identified. A total of 217 ink standards were analyzed. As inkjet printing often involves the use of multiple colors (e.g., cyan, magenta, yellow, and black) to form an image or text, two different approaches to creating a library of standards and sampling methods were evaluated for implementation in a standard operating procedure. This research will show that a microscopic examination of the region of interest is requisite to identify what colors were utilized during the printing process, prior to comparing with known standards. Finally, blind testing was administered with 10 unknown samples to assess the validity and accuracy of the methodology.